Si1−xGex nanowire based metal‐semiconductor‐metal Schottky biristor: Design and sensitivity analysis - Shaleen Nr; Sangeeta Singh; Pankaj Kumar (IET Circuits, Devices and Systems)
Abstract The incorporation of Si1−xGex nanowire based metal‐semiconductor‐metal (MSM) Schottky biristor allows the conceptualization and realization of low latch‐up and latch‐down voltages with retained latching window. With the aim of investigating the device governing physics and device performance, mathematical simulation is carried out using exhaustive and calibrated 2D Technology computer‐aided design (TCAD) device simulation. The device performance is investigated with respect to channel doping, electrode work function, channel length, temperature and mole fraction (x) to maximize the latching window size and minimize the latch‐up voltage. The detailed sensitivity analysis is also carried for the proposed device with parametric sweep method.